Measuring lupus arthritis activity using contrasted high-field MRI. Associations with clinical measures of disease activity and novel patterns of disease. Issue 1 (26th July 2018) - Zollars, Eric S; Hyer, Madison; Wolf, Bethany; Chapin, Russell
Abstract : Objective: Arthritis in SLE is poorly described, and there is no objective measure for quantification of arthritis. In this pilot study, we aim to assess the utility of the Rheumatoid Arthritis MRI Scoring System (RAMRIS) for the quantification of lupus arthritis. Methods: Patients were eligible for entry into the study if they were evaluated at the Medical University of South Carolina Lupus Center and determined by their treating rheumatologist to have active hand arthritis due to SLE. Standard of care lupus activity measures were collected, along with a detailed physical exam. MRIs were obtained using standard musculoskeletal sequences with gadolinium contrast. Semiquantitative scoring of the images used the Outcome Measures in Rheumatology Clinical Trials RAMRIS system. Results: RAMRIS demonstrates large amounts of synovitis, tenosynovitis, bone marrow oedema and erosive disease in only a minority of patients. Some patients were not scored as having any synovitis or tenosynovitis. We describe potential features of lupus arthritis that are not captured in the RAMRIS scores and may be contributing to symptoms. Conclusion: Lupus arthritis is an entity separate from rheumatoid arthritis and requires the development of new quantitative methods to describe and quantitate it. MRI findings suggest the inadequacy of a typical lupus musculoskeletal measure including swollen/tender joint counts to assess the level of disease activity.